Antibody Response of Heterologous vs Homologous Messenger RNA Vaccine Boosters Against the Severe Acute Respiratory Syndrome Coronavirus 2 Omicron Variant: Interim Results from the PRIBIVAC Study, a Randomized Clinical Trial. (11th May 2022) - Poh, Xuan Ying; Tan, Chee Wah; Lee, I Russel; Chavatte, Jean-Marc; Fong, Siew-Wai; Prince, Tessa; Hartley, Catherine; Yeoh, Aileen Y Y; Rao, Suma; Chia, Po Ying; Ong, Sean W X; Lee, Tau Hong; et al.
Abstract: Background: Waning antibody levels post-vaccination and the emergence of variants of concern (VOCs) capable of evading protective immunity have raised the need for booster vaccinations. However, which combination of coronavirus disease 2019 (COVID-19) vaccines offers the strongest immune response against the Omicron variant is unknown. Methods: This randomized, participant-blinded, controlled trial assessed the reactogenicity and immunogenicity of different COVID-19 vaccine booster combinations. A total of 100 BNT162b2-vaccinated individuals were enrolled and randomized 1:1 to either homologous (BNT162b2 + BNT162b2 + BNT162b2; "BBB") or heterologous messenger RNA (mRNA) (BNT162b2 + BNT162b2 + mRNA-1273; "BBM") booster vaccine. The primary end point was the level of neutralizing antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) wild-type and VOCs at day 28. Results: A total of 51 participants were allocated to BBB and 49 to BBM; 50 and 48, respectively, were analyzed for safety and immunogenicity outcomes. At day 28 post-boost, mean SARS-CoV-2 spike antibody titers were lower with BBB (22 382 IU/mL; 95% confidence interval [CI], 18 210 to 27 517) vs BBM (29 751 IU/mL; 95% CI, 25 281 to 35 011; P = .034) as was the median level of neutralizing antibodies: BBB 99.0% (interquartile range [IQR], 97.9% to 99.3%) vs BBM 99.3% (IQR, 98.8% to 99.5%; P = .021). On subgroup analysis, significant higher mean spike antibody titer, median surrogate neutralizing antibody level against all VOCs, and live Omicron neutralization titer were observed only in older adults receiving BBM. Both vaccines were well tolerated. Conclusions: Heterologous mRNA-1273 booster vaccination compared with homologous BNT123b2 induced a stronger neutralizing response against the Omicron variant in older individuals. Clinical Trials Registration: NCT05142319. Abstract : Spike antibody titers, surrogate virus neutralizing test levels, and live virus neutralization against severe acute respiratory syndrome coronavirus 2 wild-type, Omicron, and other variants of concern were significantly higher in older BNT162b2-vaccinated individuals who received messenger RNA-1273 compared with BNT162b2 as a booster.